ما جاءَ على غيرِ حالِهِ مِنْ كلامِ العربِ في بابِ الأفعالِ /The unusual verb structure in Arabic Utterance - ali Musa, Said; Ahmad Al-Tini, Yahya (مجلة الدراسات اللغوية والأدبية (Journal of Linguistic and Literary Studies), 2019)
ملخص البحث: يهدف البحث إلى الإتيان على المواضع التي خرجت عن كلام العرب في باب الأفعال، وبيان تعليلات النحويين وتأويلاتهم لها، ولإنجازه أُتبع المنهج الوصفي الاستقرائي، وقُسّم البحث إلى ثلاثة مباحث، المبحثُ الأولُ: ما جاءَ على غيرِ حالِهِ من الأفعالِ الناسخةِ وما في معناها، والمبحث الثاني: ما جاء على غير حاله من تعدي اللازم بنفسه، والمبحث الثالث: ما جاء على غير حاله من الأفعال لأغراض معنوية خاصة. من أبرز نتائجه: أنه ظهر من خلال هذه الدراسة أهمية الدراسة الأصولية، والتعليلات والتأويلات النحوية، ومما جاء على غير حاله استخدام كان لغير المضي، ومجيء خبر الفعل الناسخ (عسى) مفرداً، ومشابهة جاءَ ونظائره لــ: (صار الناسخة)، والأفعال التي تأتي لأغراض معنوية مثل فعلي التعجب، ونعم وبئس، وحبذا ولا حبذا. الكلمات المفتاحية: الدراسة الأصولية-ما جاءَ على غيرِ حالِهِ– كلام العرب–الأفعال. Abstract This research aims to shed light on unusual verb structures in Arabic and the justifications provided by the grammarians. It follows a descriptive approach and comes in three topics: The first deals with the unusual structures in the verbs that change the last vowel and the meaning of the subject and predicate (nÉsikh), the second deals with the unusual structures of the intransitive verbs. The third deals with the unusual structures of the verbs with special purposes. Among the most important conclusions of the study: the importance of fundamental studies was felt in this undertaking; the grammatical justifications and interpretation; the unusual structure has its own usage of changing the last vowel of the subject and predicate of the sentence similar to the function of the implicit verbs such as in the exclamation of surprise (taÑajjub), niÑma and bi’sa, ÍabbazÉ and lÉ habbazÉ. Keywords: Unusual structure – Arabic verbs – deeds Abstrak Kajian ini bertujuan membincangkan struktur kata kerja perbuatan luar biasa dalam Bahasa Arab dan sebab-sebab yang telah dikemukan oleh para pakar tatabahasa Arab. Ia menggunakan pendekatan deskriptif dan mengandungi tiga topik: Yang pertama membincangkan struktur luar biasa kata perbuatan dalam kata kerja yang berfungsi menukarkan baris akhir dan makna subjek dan predikat (nÉsikh), keduanya membincangkan struktur luar biasa kata kerja intransitif. Ketiganya membincangkan struktur luar biasa kata kerja yang mempunyai tujuan-tujuan tertentu. Di antara kesimpulan terpenting kajian ialah: kajian asas amat diperlukan dalam pengkajian isu ini yang merupakan sebab-sebab yang berkaitan tatabahasa dan interpretasi; strutur luar biasa itu mempunyai kegunaannya yang tersendiri yang menukarkan vowel terkahir subjek dan perdikat sesuatu ayat yang merupakan satu fungsi serupa dengan fungsi kata-kata kerja implisit seperti (taÑajjub), niÑma and bi’sa, ÍabbazÉ and lÉ habbazÉ. Kata kunci: Struktur luar biasa – Kata kerja – Perbuatan- perbuatan.